2010
DOI: 10.1097/ta.0b013e3181caab8f
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Obtaining Family Consent for Potential Organ Donors

Abstract: Several barriers exist to family consent for successful organ donation. Family members of minority populations, medical brain deaths, and older potential donors more often decline consent for organ donation. Family education and resource utilization toward these specific populations of potential organ donors may help to improve organ donation consent rates. In addition, delayed family approach by OPO seems to be associated with decreased consent rates. System improvements to expedite family approach by OPO may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
1
15

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(87 citation statements)
references
References 15 publications
4
67
1
15
Order By: Relevance
“…Several studies have identified factors that affect familial approval, these include perceived quality of care, knowledge of brain death/prognostic implications, health care team approach to organ donation discussions, training level of organ transplantation team representative, age of patient, medical versus trauma-related death, and timing/ setting of discussion. 5,6 Health care team-to-family communication is critical in improving consent rates for organ donationV especially concerning which health care team member approaches the family and also the timing of such interactions. Many studies have revealed the importance of clear communication by the primary physician concerning prognosis, followed closely in time with discussion by an organ procurement team representative, well trained in family dynamics/grieving processes.…”
mentioning
confidence: 99%
“…Several studies have identified factors that affect familial approval, these include perceived quality of care, knowledge of brain death/prognostic implications, health care team approach to organ donation discussions, training level of organ transplantation team representative, age of patient, medical versus trauma-related death, and timing/ setting of discussion. 5,6 Health care team-to-family communication is critical in improving consent rates for organ donationV especially concerning which health care team member approaches the family and also the timing of such interactions. Many studies have revealed the importance of clear communication by the primary physician concerning prognosis, followed closely in time with discussion by an organ procurement team representative, well trained in family dynamics/grieving processes.…”
mentioning
confidence: 99%
“…Son on yılda 50 yaşın üzerinde hayattayken yapılan bağışların sayısı artmasına rağmen, genellikle yaşlı yetişkinler organ bağışçısı olmak konusunda daha az istekli görülmüşlerdir. Bunun nedeni yaşlı vericilerin ve onların yerine karar verenlerin önyargıyla yaklaşmaları ve ileri yaşa bağlı olarak organların transplantasyon için uygun olmayacağını düşünmeleri ve ailelerin de onların algılamalarıyla düşünmeye çalışıp karar vermelerinden olabilir (7,19).…”
Section: Türk Nefroloji Diyaliz Ve Transplantasyon Dergisi Turkish Neunclassified
“…2011 yılında Amerika Birleşik Devletlerinin organ nakli bekleme listesinde 110.000'in üstünde kayıtlı hasta olduğu ve bu hastaların sadece yıllık olarak dörtte birinin canlıdan ve kadavradan yapılan nakille hayatta kalabildiği bildirilmiştir. Bununla birlikte tüm dünyada bekleme listeleri her geçen yıl daha da kalabalıklaşmaktadır (7,8 Organ nakillerinin artması, bağış sayılarının artmasına bağlıdır. Bağış sayılarının artması ise konu hakkında yeterli ve doğru bir bilincin oluşturulması ile mümkündür.…”
Section: Introductionunclassified
“…265 This gap can be reduced by separating (decoupling) the communication of brain death from the discussion of organ donation, 266 optimizing the identification of potential donors, 267 and ensuring timely communication with the organ procurement agency. 268 Programs that incorporate an in-house presence of the coordinator from the organ procurement agency can be effective in achieving these goals. 269 In addition, although the concept of brain death is widely accepted, policies and procedure to determine brain death are highly variable across states, and even across leading hospitals in the same region.…”
Section: Brain Death and Organ Donationmentioning
confidence: 99%